Famous after Death: The Effect of a Writer's Death on Book Sales - Michela Ponzo; Vincenzo Scoppa (Institute of Labor Economics (IZA), 2022)
In the standard neoclassical model consumers use all the available information and the demand for goods depends exclusively on preferences and prices whereas other spurious information do not play any role. In the market for books, we investigate if – in contrast to the standard model – the death of a writer has an impact on demand for his/her books, that is, we ask if consumers are affected by factors such as emotions and limited attention, as highlighted in behavioral economics. We use bestseller lists at week level for about 30 years (1975-2005) and through a Regression Discontinuity Design we evaluate the impact of a writer's death on the probability of entering in the bestseller list in the period immediately following his/her death. Controlling for age, gender, literary prizes, publishers' relevance and time dummies we find that a writer's death increases the probability of being in the bestseller list of more than 100%. Using a non-parametric RD approach we find very similar results. A number of robustness checks – changing the time window around the death, the estimation method, the outcome variable, the sample used – confirm our findings. In the attempt to investigate which mechanism drives consumers' decisions, we find a much greater impact for writers dying at an early age, for more famous writers and when the news is covered more extensively, suggesting that emotions and media attention are the main drivers of the impact.
Keywords: D91; Z10; Z11; L82; M30; D12; 330; book sales; writer's death; emotions; limited attention; salience; cultural economics; behavioral economics